Effect of Applied Pressure on the Mechanical Properties of 6061 Aluminum Alloy Welded Joints Prepared by Friction Stir Welding - Al-jarrah, J. A.; Ibrahim, A.; Sawlaha, S. (Engineering, Technology & Applied Science Research, 2017)
This paper investigates the effect of axial force on the surface appearance and mechanical properties of 6061 aluminum alloy welded joints prepared by friction stir welding. The applied pressure varies from 1.44 to 10.07 MPa. The applied pressure was calculated from the axial force which exerted by a spring loaded cell designed for this purpose. Defect free joints obtained at an applied pressure of 3.62 MPa. The mechanical properties of the welded joints were evaluated through microhardness and tensile tests at room temperature. From this investigation, it was found that the joint produced with an applied pressure of 5.76 MPa exhibits superior tensile strength compared to other welded joints. The fracture of this joint happened at the base material.